Spatial Analysis for Prioritizing Flood Inundation Mitigation Using the Topographic Wetness Index: A Case Study of Pangkal Pinang City - Hadi Fitriansyah; Fadiah Izzah Ajrina; Muhammad Yusuf Caesar; Haya Aqilah Maulidya; Tirta Mustika (Electronic Journal of Education, Social Economics and Technology, 2025)
Flooding is a recurring environmental challenge in Pangkal Pinang City, influenced by both natural topographic conditions and increasingly intensive land use changes. This study aims to assess spatial flood risk using the Topographic Wetness Index (TWI) as a hydrological indicator derived from Digital Elevation Model (DEM) data. Through slope and flow accumulation analysis, TWI values were calculated and classified using the equal interval method into five classes: very low, low, medium, high, and very high. The results show that the majority of the area falls into the very low and low categories, indicating good drainage conditions. However, localized zones of high and very high TWI values were identified in Bukit Intan, Gabek, and Rangkui sub-districts. In Bukit Intan, high flood susceptibility is linked to large-scale land clearing for industrial areas, residential expansion, and fish ponds. In Gabek, extensive deforestation for new settlements contributes to increasing flood risks. Meanwhile, in Rangkui, the accumulation of water is exacerbated by the density of existing built-up areas and insufficient drainage infrastructure. These findings highlight the relevance of TWI as a spatial analysis tool to support urban flood mitigation planning, especially in areas undergoing rapid land conversion. The study emphasizes the need to integrate topographic analysis into urban development policies to ensure flood-resilient growth.